Mycobacterium Biofilms - Esteban, Jaime; García-Coca, Marta (Frontiers in Microbiology, 2018)
The genus Mycobacterium includes human pathogens (Mycobacterium tuberculosis and Mycobacterium leprae) and environmental organisms known as nontuberculous mycobacteria (NTM) that, when associated with biomaterials and chronic disease, can cause human infections. A common pathogenic factor of mycobacteria is the formation of biofilms. Various molecules are involved in this process, including glycopeptidolipids, shorter-chain mycolic acids, and GroEL1 chaperone. Nutrients, ions, and carbon sources influence bacterial behavior and have a regulatory role in biofilm formation. The ultrastructure of mycobacterial biofilms can be studied by confocal laser scanning microscopy, a technique that reveals different phenotypic characteristics. Cording is associated with NTM pathogenicity, and is also considered an important property of M. tuberculosis strains. Mycobacterial biofilms are more resistant to environmental aggressions and disinfectants than the planktonic form. Biofilm-forming mycobacteria have been reported in many environmental studies, especially in water systems. NTM cause respiratory disease in patients with underlying diseases, such as old tuberculosis scars, bronchiectasis, and cystic fibrosis. Pathogens can be either slowly growing mycobacteria, such as Mycobacterium avium complex, or rapidly growing species, such as Mycobacterium abscessus. Another important biofilm-related group of infections are those associated with biomaterials, and in this setting the most frequently isolated organisms are rapidly growing mycobacteria. M. tuberculosis can develop a biofilm which plays a role in the process of casseous necrosis and cavity formation in lung tissue. M. tuberculosis also develops biofilms on clinical biomaterials. Biofilm development is an important factor for antimicrobial resistance, as it affords protection against antibiotics that are normally active against the same bacteria in the planktonic state. This antibiotic resistance of biofilm-forming microorganisms may result in treatment failure, and biofilms have to be physically eradicated to resolve the infection. New strategies with potential antibiofilm molecules that improve treatment efficacy have been developed. A novel antibiofilm approach focuses on Methylobacterium sp. An understanding of biofilm is essential for the appropriate management of patients with many NTM diseases, while the recent discovery of M. tuberculosis biofilms opens a new research field